2021
DOI: 10.1002/anie.202107158
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Cysteine‐Free Native Chemical Ligation at Challenging Junctions with a Ligation Auxiliary Capable of Base Catalysis

Abstract: Ligation auxiliaries are used in chemical protein synthesis to extend the scope of native chemical ligation (NCL) beyond cysteine. However, auxiliary‐mediated ligations at sterically demanding junctions have been difficult. Often the thioester intermediate formed in the thiol exchange step of NCL accumulates because the subsequent S→N acyl transfer is extremely slow. Here we introduce the 2‐mercapto‐2‐(pyridin‐2‐yl)ethyl (MPyE) group as the first auxiliary designed to aid the ligation reaction by catalysis. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
(63 reference statements)
0
19
0
1
Order By: Relevance
“…173 Most recently, we introduced the 2-mercapto-2-(pyridin-2-yl)ethyl (MPyE) group, which is the first auxiliary designed to aid ligation by intramolecular base catalysis. 174 The MPyE auxiliary enables ligation at sterically hindered junctions, including proline or β-branched amino acids. At the time this review was drafted, auxiliaries have found little use so far in phosphoprotein synthesis.…”
Section: Synthesis Of Phosphoproteinsmentioning
confidence: 99%
“…173 Most recently, we introduced the 2-mercapto-2-(pyridin-2-yl)ethyl (MPyE) group, which is the first auxiliary designed to aid ligation by intramolecular base catalysis. 174 The MPyE auxiliary enables ligation at sterically hindered junctions, including proline or β-branched amino acids. At the time this review was drafted, auxiliaries have found little use so far in phosphoprotein synthesis.…”
Section: Synthesis Of Phosphoproteinsmentioning
confidence: 99%
“…Interestingly, the thioester-linked intermediate 42AN*, formed by the reaction of the selenoester with the Chemistry-A European Journal auxiliary thiol, was still detectable via UPLC analysis. This intermediate could not be observed with the MPyE auxiliary (see Figure 3 in [6]), indicating again, that the additional methoxy group moderately lowers the rate of S,N-acyl transfer. Nevertheless, complete conversion to ligated Ala-Asn peptide was observed in less than 24 h. We also tested the MMPyE auxiliary in a Leu-Val ligation using selenoesters.…”
Section: Chemistry-a European Journalmentioning
confidence: 96%
“…LYRAA-SePh (22A): Selenoester 22A was synthesized according to the published procedure. [6] UPLC-MS: t R = 5.31 min (3-30 % B in 6 min); m/z = 733.…”
Section: Synthesis Of Model Peptide Selenoestersmentioning
confidence: 99%
“…1,2 The chemospecic nature of this reaction prevents the need for the side chain protection of peptides, and thus it can be used just as effectively in recombinant protein-COSR obtained by splicing of protein-intein fusions. 3 Further elaborations of the NCL extended the reaction to other N-terminal residues, [4][5][6][7] peptide selenoesters 8 and selenoester-diselenide ligations. 9 Since Fmoc-solid phase peptide synthesis (Fmoc-SPPS) is currently the most adopted methodology for peptide synthesis, the direct preparation of peptide thioesters is poorly efficient, necessitating other approaches that overcome the piperidine-mediated aminolysis of the peptide-COSR.…”
Section: Introductionmentioning
confidence: 99%